Avoiding DWI among Bar-room Drinkers: Strategies and Predictors - Barry D. Caudill; John W. Rogers; Jan Howard; Kevin C. Frissell; Wayne M. Harding (SAGE Publishing, 2010)
We examined the prevalence and predictors of 11strategies to avoid driving when feeling intoxicated among 561 bar-room patrons in two medium-sized Maryland communities. Logistic regression analyses identified demographic, behavioral, and attitudinal predictors of avoidance strategies and interactions among predictors. Overall, 89% reported one or more DWI avoidance actions in the past year, and 38% reported driving intoxicated during that time. Average frequencies of avoidance behavior and intoxicated driving increased significantly as drinking level increased. However, the higher the drinking level, the smaller the ratio of avoidance actions to DWI experiences, highlighting the vulnerability of heavy drinkers who had driven intoxicated. Using a sober driver or one who allegedly drank less than the respondent were the most popular and frequent strategies, but paying for a cab, walking, and using a bus or free cab were relatively unpopular. Higher drinking levels predicted significantly higher odds of using avoidance approaches, as did intoxicated driving. Confidence in driving safely when intoxicated was positively related to drinking level and intoxicated driving, but it tended to predict lower odds of avoidance actions. Similarly, marital status, age, gender, and location influenced the odds of avoidance behaviors. Interventions should be strategically tailored to exploit or counter drinker predilections among avoidance options.